Pemetaan dan Analisis Tingkat Kebisingan di Kawasan Pelabuhan Tanjung Perak Menggunakan Software Surfer - Praditya Sigit Ardisty Sitogasa; Sella Olivia Fitriani (Prosiding ESEC, 2023)
Tanjung Perak is one of the port areas with a very dense industry and can support the hinterland around Tanjung Perak. With the density of the industry, the noise level from industrial operations continues to increase. With the increase in operational activities, several measures are needed to reduce noise levels from ongoing operational activities. From this statement, this research is aimed at finding out the distribution of noise levels in a day so that a solution is found to reduce noise levels in the Tanjung Perak industrial area. The research location is a maritime service industry whose operational activities take place every day. For noise sampling carried out at 7 points in the industry. After the noise test is carried out, the data will be modeled into surfer software to determine the distribution of noise levels in industrial areas. After being modeled through surfer software, it will later be imaged through Google Earth. The modeling results show that the greatest fatigue occurs during the day due to high operational activities. With these results, it is hoped that the industrial area can implement a policy for all workers to use ear protection devices so that the noise level that occurs in areas with the highest noise can be reduced and does not interfere with the ear health of workers.